Leopardi and mesmerism: a magnetic reading of Tasso (ENTHYMEMA, 2021)
Mesmerism, also known as animal magnetism, inspired a magnetic literature which achieved resounding success in Europe (especially in France, Germany and England) and in the US throughout the 19th century. Franz Anton Mesmer (1734-1815) theorized this set of practices which constituted the first psychotherapeutic system and inaugurated numerous studies on hypnotism. In the Italian context, Giacomo Leopardi was the first writer to represent mesmeric imaginary in his literary works. In this article, I will analyze various works by the poet from Recanati and, in particular, I will propose a mesmeric reading of ‘Dialogo di Torquato Tasso e del suo Genio familiare’.
Keywords: Mesmerism; hypnotism; unconscious; memory; dream